1999
DOI: 10.1073/pnas.96.23.13312
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hemochromatosis due to MHC class I HFE deficiency: Immune status and iron metabolism

Abstract: The puzzling linkage between genetic hemochromatosis and histocompatibility loci became even more so when the gene involved, HFE, was identified. Indeed, within the well defined, mainly peptide-binding, MHC class I family of molecules, HFE seems to perform an unusual yet essential function. As yet, our understanding of HFE function in iron homeostasis is only partial; an even more open question is its possible role in the immune system. To advance on both of these avenues, we report the deletion of HFE ␣1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 30 publications
9
119
1
Order By: Relevance
“…Although we did not measure dietary iron absorption in this study, two other studies (25,27) have shown that the absorption of luminal iron by the duodenum was increased in the Hfe KO mice compared with the control mice. This finding could be explained by the results of the present study showing impaired uptake of transferrin-bound iron from plasma by the cells in the crypt region of the duodenum in Hfe KO mice compared with that seen in the control mice.…”
Section: Discussionmentioning
confidence: 90%
“…Although we did not measure dietary iron absorption in this study, two other studies (25,27) have shown that the absorption of luminal iron by the duodenum was increased in the Hfe KO mice compared with the control mice. This finding could be explained by the results of the present study showing impaired uptake of transferrin-bound iron from plasma by the cells in the crypt region of the duodenum in Hfe KO mice compared with that seen in the control mice.…”
Section: Discussionmentioning
confidence: 90%
“…In HH patients, it is postulated that HFE mutations result in the impairment of HFE function in duodenal crypt cells (46,47). In the mouse models of HH, loss of HFE function results both from the C282Y mutation or knockout mutations in the HFE gene and from deficiency of ␤ 2 M as in the ␤ 2 M-knockout mouse (11)(12)(13)(14)(15). In fact, the discovery that ␤ 2 M-deficient mice show an HH phenotype was the initial piece of evidence associating MHC class I-type proteins in iron homeostasis and in HH (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting question is whether mutant HFEs will behave like HFE expressed in the absence of ␤ 2 M in CHO and TRVb-1 cells. Because HFE knockout and C282Y mutant mice behave phenotypically like ␤ 2 M-deficient mice, i.e., both have the murine HH phenotype, one would predict that they would (11)(12)(13)(14)(15). By analogy with the role of HFE-␤ 2 M in modulating uptake of Tf-Fe by CHO and TRVb-1 cells, we suggest: (i) that HFE-␤ 2 M normally plays a role in facilitating uptake of Tf-bound iron by duodenal crypt cells and macrophages; (ii) that HFE mutations that impair this function in HH patients contribute to dysregulation of iron absorption, because this uptake process by duodenal crypt cells is key to sensing the level of Tf-bound iron in capillaries surrounding crypt cells of the duodenum where iron absorption is controlled (48,50,51); and (iii) this impairment of Tf-bound iron uptake leads the duodenal crypt cells to be iron poor (47)(48)(49)52), even in the face of body iron excess, and to program cells differentiating into mature villus cells to absorb excess iron in HH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice deficient in ␤ 2 M and mice deficient in Hfe or engineered to express the disease-associated C282Y HFE mutation demonstrate systemic iron overload with iron deposition in liver parenchymal cells (11)(12)(13)(14)(15)(16). The B2m null (Ϫ) mutation has been highly back-crossed onto an array of inbred mouse strain backgrounds (17)(18)(19).…”
mentioning
confidence: 99%